2020
DOI: 10.1039/d0nj00659a
|View full text |Cite
|
Sign up to set email alerts
|

Development of light-emitting liquid-crystalline polymers with a pentafluorinated bistolane-based luminophore

Abstract: Light-emitting liquid-crystalline polymers showing PL in the pristine solid state can control their PL color from blue to light-blue via a thermal phase transition to LC phases, which originates from a dynamic change of aggregated structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In contrast to the PL behavior of 2a-f in CH 2 Cl 2 solution as mentioned above, the PL spectral shape as well as λ PL were found to significantly change with the alkylene linkage length. Based on our prior knowledge on PL behavior in crystalline states [22][23][24][25][26][27][28], the large differences among PL behavior of 2a-f in the crystalline powder state was likely attributable to the distinct intermolecular interactions between neighboring molecules, although no odd-even effect was noted in the PL behavior of the crystalline powder state samples of dyads 2a-f. In sharp contrast to the Φ PL of 2a-f in the solution state, the Φ PL of 2a-f in the crystalline powder state was found to increase up to 0.56, which was possibly due to the significant suppression of non-radiative deactivation induced by molecular motions by the formation of molecular aggregates via intermolecular interactions.…”
Section: Photophysical Behavior In Crystalline Powder Statementioning
confidence: 97%
See 1 more Smart Citation
“…In contrast to the PL behavior of 2a-f in CH 2 Cl 2 solution as mentioned above, the PL spectral shape as well as λ PL were found to significantly change with the alkylene linkage length. Based on our prior knowledge on PL behavior in crystalline states [22][23][24][25][26][27][28], the large differences among PL behavior of 2a-f in the crystalline powder state was likely attributable to the distinct intermolecular interactions between neighboring molecules, although no odd-even effect was noted in the PL behavior of the crystalline powder state samples of dyads 2a-f. In sharp contrast to the Φ PL of 2a-f in the solution state, the Φ PL of 2a-f in the crystalline powder state was found to increase up to 0.56, which was possibly due to the significant suppression of non-radiative deactivation induced by molecular motions by the formation of molecular aggregates via intermolecular interactions.…”
Section: Photophysical Behavior In Crystalline Powder Statementioning
confidence: 97%
“…In spite of their wide utility, progress in terms of the molecular design of solid-state photoluminescent molecules has been quite limited; accordingly, the search for efficient solid-state photoluminescent molecules is still on. Since a few years ago, we have extensively developed solid-state photoluminescent molecules based on the extended π-conjugated structure containing a fluorinated aromatic structure, which induces electron-density distribution owing to its large electronegativity and forms a tight crystal structure via van der Waals and hydrogen bonding interactions [22][23][24][25][26][27][28]. Among them, polyfluorinated tolane 1a [27] displayed highly efficient blue photoluminescence (PL) (ΦPL = 0.73) in crystalline states, although the PL efficiency was observed to be significantly low in dilute solution (ΦPL = ~0.04) (Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the scope of π-conjugated photoluminescence (PL) molecules was extended to include a pentafluorinated aromatic scaffold, as exemplified by fluorinated tolanes C and bistolanes D (Figure 1a) [20][21][22]. The investigation of pentafluorinated bistolane-based PL molecules revealed that alkoxy-substituted fluorinated bistolanes E combine both PL and LC characteristics in a single molecule and therefore form light-emitting liquid crystals (PLLCs) [23][24][25][26]. Although the PL and LC behaviors of these bistolanes are significantly sensitive to electronic and molecular aggregate structures, the corresponding structure-property relationships remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Crystals 2020, 10, x FOR PEER REVIEW 2 of 15 bistolane-based PL molecules revealed that alkoxy-substituted fluorinated bistolanes E combine both PL and LC characteristics in a single molecule and therefore form light-emitting liquid crystals (PLLCs) [23][24][25][26]. Although the PL and LC behaviors of these bistolanes are significantly sensitive to electronic and molecular aggregate structures, the corresponding structure-property relationships remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…1a). [6][7][8][9] However, their syntheses require multiple synthetic steps and the total yields are low; therefore, there is tremendous interest in discovering efficient PL mesogens. Our efforts have revealed that the D-π-Atype diphenylacetylene derivative with alkoxy and cyano groups at the respective longitudinal terminals exhibits PL in solution and in the crystalline phase, which makes it a promising candidate as an alternative PL mesogen (Fig.…”
mentioning
confidence: 99%